1980
DOI: 10.1111/j.1740-8261.1980.tb00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Emphysematous Cholecystitis in the Nondiabetic Dog: Three Case Histories

Abstract: Emphysematous cholecystitis not associated with diabetes mellitus was diagnosed in three dogs. All three dogs were examined because of vomiting. Neutrophilia, elevated serum alkaline phosphatase, and normal serum glucose were present in each animal. A gas-filled gallbladder and pericholecystic gas were seen radiographically in all three dogs; a cholecystolith was present in one dog. A cholecystectomy was performed on two dogs. Cultures of bacteria from these two bladders revealed Clostridium sp. One of these d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Furthermore, cholecystocentesis is contraindicated in emphysematous cholecystitis, as indicated by the presence of intraluminal gas. In these instances sepsis secondary to anaerobic bacterial infection is likely (Burk andJohnson 1980, Center 1996). Ischaemia and tissue necrosis are features of anaerobic bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cholecystocentesis is contraindicated in emphysematous cholecystitis, as indicated by the presence of intraluminal gas. In these instances sepsis secondary to anaerobic bacterial infection is likely (Burk andJohnson 1980, Center 1996). Ischaemia and tissue necrosis are features of anaerobic bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…One additional case also showed changes suggestive of concurrent cholecystitis (Spaulding 1993), but samples were not taken to confirm this histopathologically. There are a number of case reports in the literature documenting acute cholecystitis (Lord and Wilkins 1972, Burk and Johnson 1980, Oswald and others 1994). Church and Matthiesen (1988) reported a large retrospective study of dogs with necrotising cholecystitis and suggested that in many cases this reflected acute exacerbation of a chronic cholecystitis.…”
Section: Discussionmentioning
confidence: 99%
“…l~~ Biliary tract emphysema can occur secondary to surgical intervention, reflux of gas from the duodenum, or infection by gas producing organisms.2 Gas in the biliary tree appears on radiographs as small linear or circular lucencies in the hepatic paren~hyma.~ Emphysematous cholecystitis in dogs is most often associated with poorly regulated diabetes mellitus; however, it has been reported in non-diabetic anim a l~.~ Radiographic lucencies are noted within the wall or lumen of the gallbladder. [2][3][4][5][6] Gas can be found in the portal venous system secondary to gastric dilatation-volvulus, severe necrotic proximal gastroenteritis, or functional ileus, and generally carries a poor prognosis. 2 The radiographic pattern of gas in the portal system is linear and branching, much like air bronchograms.…”
Section: Discussionmentioning
confidence: 99%